Integrating the Software Development Lifecycle into Work-Integrated Learning: : A Case Study at a South African University of Technology - Mbele, Mpho; Swart, James Swart (International Journal of Research in STEM Education, 2024)
Work-integrated learning is crucial for student development, providing hands-on experience in industry placements or project-based learning at higher educational institutions. This article evaluates the impact of adopting a Software Development Lifecycle (SDLC) process in work-integrated learning software development projects at a University of Technology. Comparing two student projects, the waterfall model resulted in substandard conversion between class diagrams and route classes, while the agile model allowed frequent reviews and modifications, resulting in alignment between class diagrams and route classes. The key difference was the absence of clear directional indicators and comprehensive descriptions of class relationships. It is recommended that students adopt an appropriate SDLC model that meets their specific project needs within a work-integrated learning environment.